PERBEDAAN HASIL BELAJAR SISWA MENGGUNAKAN MEDIA AUDIO VISUAL (CD INTERAKTIF) DENGAN MEDIA GAMBAR PADA MATA PELAJARAN IPA KELAS V SEMESTER I DI GUGUS 1 KENDIT TAHUN PELAJARAN 2016-2017 - Yunita Erisanti; Vidya Pratiwi (Jurnal IKA PGSD (Ikatan Alumni PGSD) UNARS, 2016)
The purpose of this research is to know is there any significant difference to student learning outcomes using audio-visual media (interactive CD) with image media in science subjects in the first semester of the fifth grade group 1 gird the academic year 2016-2017. This study uses research experimental class and control class. The research design used ini this experiment, which is a type Two Group Posstest only because of the subject there is no difference between the experimental group with an average score of the controll group. Subjects used were all students of class V SDN 2 Kendit and class V SDN 5 Kendit by the number of students 34 students. Data collection techniques used in this study is testing techniques. Data collection instrument in the form of sheets of test item. The data analysis result score learnscience using t-test with the help of Microsoft Excel 2013